COVID-19 Vaccine Hesitancy among Library Professionals: A Case Study of Indian Health Science Librarians. Issue 3 (3rd July 2022) - Kumar Verma, Manoj; Khan, Daud; Yuvaraj, Mayank
ABSTRACT: This article aims to identify the factors prevalent among health science librarians toward vaccine hesitancy. With the development of COVID-19 vaccines in 2021, numerous efforts are being taken to vaccinate people to control the spread of coronavirus. Recent research has shown a high level of vaccine hesitancy among various groups in various fields but no study has been conducted to explore the factors responsible for vaccine hesitancy among library professionals. A cross-sectional online survey of Indian health science librarians was conducted. Data was collected through an online questionnaire designed on Google Forms and analyzed using MS-Excel. Descriptive statistics were used in the study. The majority of respondents (77%) showed a high level of vaccine hesitancy due to issues of safety, negative information, and confusion over vaccines. Measures to increase vaccination uptake and authentic sources with respect to COVID-19 vaccines have been discussed.